A Re-examination of Potosí Applique Censers from Greater Nicoya - Platz, Lorelei (Universidad de Costa Rica, 2017)
From approximately AD 100–1250, Potosí Applique varieties were manufactured and consumed in both the northern (Nicaragua) and southern (Costa Rica) sectors of Greater Nicoya. These two-part ceramic objects consist of a dish-form base and a tall, generally ‘bell-shaped’ lid. The ceramic type name takes its descriptor from the generous use of plastic applique decoration adorning the vessel bodies. These objects were used for burning incense, and the lid portion of the vessel is typically understood to represent an actual landscape feature, such as a mountain or volcano, providing physical context for modelled figures seen frequently atop the lid. Published examples tend to feature fantastic crocodiles, seated humans or, less frequently, jaguars, and all of which have been linked with ritual aspects of shamanic transformation in Greater Nicoya. Here I argue that traditional interpretations of Potosí Applique are limited in their focus and thus their ability to deepen our understanding of the vessel class itself, as well as the wide array of ritual imagery and cultural messages it likely communicated in ancient times. While maintaining focus on important aspects of ritual practice and the relationship between the supernatural and spiritual transformation, this preliminary re-analysis indicates that Potosí vessels present important and unexplored representations of flora. Plants, and all their component parts (flowers, leaves, fruit, seeds, etc.)—whether offered, ingested, or burned for ceremonial purposes—likely played an important role in various types of ceremonies including mortuary, healing, and transformation, among others, and are discussed here as potential avenues for future research.